Limites às convenções processuais na sistemática recursal do processo civil democrático - Tiago Augusto Leite Retes (2018)
This paper aims to set the procedural agreements within the new guise of civil procedural law, in which there is a strong presence of the right to freedom in its formation, to then structure a methodology of control of the procedural agreements and, finally, to promote its test in the appeal systematics. In order to clarify the reason for the acceptance of freedom as a structuring element of the process, the historical evolution of the procedural agreements is analyzed, as well as its influence on the process dynamics. It shows how business deals can be beneficial and can bring benefits to individuals. The need for them to be controlled, presenting methods from other areas of law, is emphasized in order to try to transplant them into the civil procedure. Concepts that are considered useless or inconclusive within a solid theory, although adopted in large scale by legal literature, are removed. A structure of control of the procedural business is built, based on the hard core of procedural principles, and its testing in the appeal system is carried out, with a view to the applicability of the institute and its transforming potential.